Seven Versus 14 Days of Antibiotic Therapy for Uncomplicated Gram-negative Bacteremia: A Noninferiority Randomized Controlled Trial. (11th December 2018) - Yahav, Dafna; Franceschini, Erica; Koppel, Fidi; Turjeman, Adi; Babich, Tanya; Bitterman, Roni; Neuberger, Ami; Ghanem-Zoubi, Nesrin; Santoro, Antonella; Eliakim-Raz, Noa; Pertzov, Barak; Steinmetz, Tali; et al.
Abstract: Background: Gram-negative bacteremia is a major cause of morbidity and mortality in hospitalized patients. Data to guide the duration of antibiotic therapy are limited. Methods: This was a randomized, multicenter, open-label, noninferiority trial. Inpatients with gram-negative bacteremia, who were afebrile and hemodynamically stable for at least 48 hours, were randomized to receive 7 days (intervention) or 14 days (control) of covering antibiotic therapy. Patients with uncontrolled focus of infection were excluded. The primary outcome at 90 days was a composite of all-cause mortality; relapse, suppurative, or distant complications; and readmission or extended hospitalization (>14 days). The noninferiority margin was set at 10%. Results: We included 604 patients (306 intervention, 298 control) between January 2013 and August 2017 in 3 centers in Israel and Italy. The source of the infection was urinary in 411 of 604 patients (68%); causative pathogens were mainly Enterobacteriaceae (543/604 [90%]). A 7-day difference in the median duration of covering antibiotics was achieved. The primary outcome occurred in 140 of 306 patients (45.8%) in the 7-day group vs 144 of 298 (48.3%) in the 14-day group (risk difference, –2.6% [95% confidence interval, –10.5% to 5.3%]). No significant differences were observed in all other outcomes and adverse events, except for a shorter time to return to baseline functional status in the short-course therapy arm. Conclusions: In patients hospitalized with gram-negative bacteremia achieving clinical stability before day 7, an antibiotic course of 7 days was noninferior to 14 days. Reducing antibiotic treatment for uncomplicated gram-negative bacteremia to 7 days is an important antibiotic stewardship intervention. Clinical Trials Registration: NCT01737320. Abstract : Shortening antibiotic duration is important for antimicrobial stewardship. This randomized controlled trial showed noninferiority of 7 days compared with 14 days of covering antibiotics for patients with uncomplicated gram-negative bacteremia. Seven days of antibiotics is sufficient for uncomplicated gram-negative bacteremia.